Implementación de un sistema de control de temperatura y humedad en la florícola Pilatasig Analuisa Martha Cecilia ubicado en la provincia de Cotopaxi - Pilatasig Chicaiza, Henry Fabricio (2022)
The purpose of this project is to design and implement a control system that allows the acquisition of physical variables of temperature and humidity in the germination area of wallflower seeds in the greenhouse Pilatasig Analuisa Martha Cecilia, in order to perform the automation process of the irrigation system and air extraction to improve the environmental conditions inside the greenhouse. To make the temperature and humidity control system, a bibliographic research was made about the climatic requirements of the wallflower flower and the irrigation processes in the cultivation area to make the design that allows detailing the technical characteristics and the cost of the materials that were used for the control system, taking as reference the use of a PLC Logo 12/24 RCE Siemens brand which provides a flexible, safe and reliable control system, In addition to being a device easy to acquire in the market and at a relatively moderate cost, which allows establishing temperature ranges between 5 to 25 ºC and a humidity percentage between 50 and 70 %, if the maximum temperature limit is exceeded the controller allows the operation of an air extractor and if the humidity percentage is less than 50 % it will activate the water irrigation system, systems that will be in operation until the established parameters are reached.